Xylolentia bambusae (Rhamphoriaceae, Rhamphoriales), a novel species associated with dead bamboo in Guangdong Province, China - Zhao, Haijun; Mapook, Ausana; Hyde, Kevin D.; Doilom, Mingkwan; Al-Otibi, Fatimah O.; Saichana, Natsaran; Dong, Wei (Phytotaxa, 2025)
Species within Rhamphoriaceae are distributed in both terrestrial and aquatic habitats worldwide, yet the investigation into their distribution and diversity in South China remains insufficient. Through a comprehensive morphological assessment and phylogenetic analysis utilizing a combined dataset of ITS, LSU, SSU, tef1-α, and rpb2 sequences, we have isolated and identified a novel species, Xylolentia bambusae, in Rhamphoriaceae from decaying bamboo culms in Guangdong Province, China. This study provides detailed description and illustration of the novel species, along with an updated backbone tree of Rhamphoriaceae to enhance our understanding of the genera/species relationships within the family.